Ответ:
Пошаговое объяснение:
1) -2 3/7+(-7 4/7)=-10
-1 4/9+(-3 5/9)=-5
-10+(-5)=-15
2) -11 1/8+(-3 1/4)=-11 1/8-3 2/8=-14 3/8
-10 7/11+(-4 4/11)=-15
-15+(-14 3/8)=-29 3/8
3) -5 1/3+(-2/3)=-6
-6+(-2 3/5)=-8 3/5
4) -2 1/3+(-1/6)=-2 2/6-1/6=-2 1/2
-2 1/2+(-1/2)=-3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1) -2 3/7+(-7 4/7)=-10
-1 4/9+(-3 5/9)=-5
-10+(-5)=-15
2) -11 1/8+(-3 1/4)=-11 1/8-3 2/8=-14 3/8
-10 7/11+(-4 4/11)=-15
-15+(-14 3/8)=-29 3/8
3) -5 1/3+(-2/3)=-6
-6+(-2 3/5)=-8 3/5
4) -2 1/3+(-1/6)=-2 2/6-1/6=-2 1/2
-2 1/2+(-1/2)=-3